2015
DOI: 10.1073/pnas.1514265112
|View full text |Cite
|
Sign up to set email alerts
|

Recombination patterns in maize reveal limits to crossover homeostasis

Abstract: During meiotic recombination, double-strand breaks (DSBs) are formed in chromosomal DNA and then repaired as either crossovers (COs) or non-crossovers (NCOs). In most taxa, the number of DSBs vastly exceeds the number of COs. COs are required for generating genetic diversity in the progeny, as well as proper chromosome segregation. Their formation is tightly controlled so that there is at least one CO per pair of homologous chromosomes whereas the maximum number of COs per chromosome pair is fairly limited. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 53 publications
6
61
0
1
Order By: Relevance
“…Crossover homeostasis was first described in S. cerevisiae and has since been described in S. pombe , C. elegans , maize, and mouse (50, 108, 147, 202, 231, 232). Crossover homeostasis, as initially defined, is the maintenance of crossover frequency even when precursor DSB numbers are decreased (147).…”
Section: Mechanisms Governing Crossoversmentioning
confidence: 99%
See 1 more Smart Citation
“…Crossover homeostasis was first described in S. cerevisiae and has since been described in S. pombe , C. elegans , maize, and mouse (50, 108, 147, 202, 231, 232). Crossover homeostasis, as initially defined, is the maintenance of crossover frequency even when precursor DSB numbers are decreased (147).…”
Section: Mechanisms Governing Crossoversmentioning
confidence: 99%
“…In maize, for example, Sidhu et al (202) analyzed strains with varying numbers of meiotic DSBs, as measured by RAD51 foci. Interestingly, they found that crossover numbers increased accordingly, suggesting that perhaps homeostasis mechanisms are different in plants.…”
Section: Mechanisms Governing Crossoversmentioning
confidence: 99%
“…Finally, CO homeostasis, which has been documented in S. cerevisiae and mouse, can maintain a stable number of COs even when DSB numbers are altered (Martini et al, 2006). However, a recent study suggested that, at least in maize (Zea mays), CO homeostasis is not prominent (Sidhu et al, 2015), and this result may argue that plants in general do not exhibit this phenomenon.…”
Section: Dsb Repair and Their Fatesmentioning
confidence: 99%
“…Different approaches are used to determine both number and positions of COs along homologous chromosomes (Mézard et al, ): Counts of chiasmata, the cytological signatures of COs at metaphase I (Sidhu et al, ), with the risk of missing some chiasmata and thus COs owing to the highly compacted state of metaphase chromosomes. Analysis of protein complexes associated with COs along the less compacted pachytene chromosomes by electron microscopy (EM; observation of late recombination nodules; Anderson et al, ) or by fluorescence microscopy using immunolocalization (Anderson, Reeves, Webb, & Ashley, ). Measuring distances between COs remains, however, time‐consuming.…”
Section: Introductionmentioning
confidence: 99%